Maladministration in Corruption Case: A Study of Limitation on the Criminal Action - Odie Faiz Guslan (Universitas Negeri Semarang, 2018)
This study aims to determine the boundaries between implementing a government agency (bestuurhandeling) that harms quality state finances as maladministration or is a criminal act of corruption. Normative juridical research methods. The results of the study show that not all companies are carried out by public officials who are financial sources of corruption. In determining the boundaries between acts of maladministration and acts of the body or government officials must avoid discretionary actions that contain legal ribbons such as: fraud (deception), manipulation, misdirection (misrepresentation), concealment of facts, breach of trust, subterfuge (subfunction), or circumvention of regulations (illegal violations).